Virtual flux direct power‐backstepping control of 5‐level T‐type multiterminal VSC‐HVDC system. (18th July 2017) - Reguig Berra, Ahmed; Barkat, Said; Bouzidi, Mansour
Summary: In this study, a nonlinear control of a 5‐level T‐type converter topology‐based multiterminal voltage source converter high‐voltage direct current system is proposed. The idea of the proposed control is to combine the backstepping control and direct power control with virtual flux concept into one controller able to improve the performance of the transmission system. In the other side, the use of a 5‐level space vector modulation with a balancing strategy based on effective use of the redundant switching states of the converters voltage vectors guarantees the objective of maintaining balanced voltages in DC‐capacitors. Finally, simulations of the 5‐level T‐type multiterminal voltage source converter high‐voltage direct current system validate the effectiveness of the proposed control law. The obtained results are compared with those performed by a conventional Proportional Integrator (PI) controller. These outcomes allow to exhibit excellent transient response during a range of operating conditions.